Impact of dynamic capabilities and digital innovation on competitiveness mediated by responsible innovation - de la Torre Rojas, Alicia Alexandra (2025)
In a dynamic global context towards digitalization, and with increasing social demands, companies face the challenge of staying competitive. This study empirically validates the relationship between dynamic capabilities (digital orientation, digital capability, and willingness to change), digital innovation, responsible innovation, and competitiveness by integrating them into a competitive and sustainable digital innovation model. This model allows companies to identify innovation strategies for sustainability that are aligned with the concept of innovability. Considering the theory of dynamic capabilities to achieve sustainable competitive advantage, a structural equation model was applied with data from 216 private Ecuadorian technology companies, which validated responsible innovation as a mediator of digital innovation, competitiveness, and dynamic capabilities as facilitators of digital innovation, responsible innovation, and its impact on competitiveness. This research contributes to business practice on the need for companies to redefine their digital innovation management strategies, incorporating dynamic capabilities for the rapid reconfiguration of resources in a changing environment and responsible innovation for sustainable competitiveness aligned with compliance with the SDGs. For future research, this model can be considered a starting point, since the mediating or moderating variables can be replicated and extended to other sectors or countries, and can be complemented with qualitative research.